Educational intervention program to promote the change of attitude toward physical activity and the improvement of the lifestyle of medical technology students in a private university - Santiago Bazán, Cristhian (2018)
Objective: To determine the influence of an educational intervention program to promote attitude changes towards physical activity and lifestyle improvement in medical technology students of a private university. Materials and methods: A quantitative, quasi-experimental, longitudinal, prospective study. The study sample included 94 students, divided into two groups: A (experimental group) and B (control group), which were created and designed by the author, and lasted 12 sessions in the Academic Semester 2016-II. Regarding the instruments used in the research, the Canopy test was used to measure the attitude towards physical activity; a 30-question questionnaire was applied to measure healthy lifestyles, resulting in a high-reliability value (Crombach's Alpha) of 0.95; and Student's t-test confirmed that there is a significant difference between pre-test and post-test averages. Results: The educational intervention program influenced the indicator "perceived importance" with p = 0.000. The attitude towards the indicator "practical activity" was p = 0.000. As for lifestyle dimensions in medical technology students, physical care dimension reached p = 0.000, social dimension p = 0.025, mental dimension p = 0.000, and moral ethical dimension p = 0.002. Conclusions: A statistically significant influence in attitude changes towards physical activity and lifestyle was demonstrated in medical technology students, which is extremely important because it enables the promotion and protection of the university community’s health by improving its quality of life.